Aplicación de procedimientos evitando errores en la presentación de la devolución de retenciones en la fuente del contribuyente Roberto Romero - Robles Romero, Maria Gabriela (2015)
The research work is directly related to existing taxes in our country, specifically the income tax and its different types of withholding by withholding agents, so called by the Internal Revenue Service for their ability to grow and volume of transactions carried out over a period of time. The work becomes a strategy to be used by different users of the information, because it is similar to several one-person and multi-person businesses, according to the requirements that are required to make a return of cash retained by clients in acquisitions the goods offered and their ability to execute in the legal framework. Additionally conclusions and recommendations aimed at improving the current situation are issued, as to not be taking the opportunity to have additional liquidity to effect an orderly request for the return of retentions made, a situation that could improve the conditions of the company in its field of liquidity and profitability. The main purpose of the work performed, is reflected in the intention of the author to run a proper and logical methodology, how to make an effective request withholding evolution and serve to strengthen entries cash, to be the engine that drives the economy in all areas.